The sub-supersolution method for partial differential equations - Zeghouma, Nadjet; Houri, Mohammed (Université of eloued جامعة الوادي, 2025)
This memory presents a study of the sub-supersolution method as a robust tool for proving the existence of solutions to nonlinear differential equations, with a focus on its application to the Kirchhoff model derived from elastic string vibrations. The methodology revolves around constructing a pair of functions (supersolution and subsolution) that bound the desired solution, followed by a generating monotonic sequence converges to it. Cette mémoire présente une étude de la méthode des sous-super solutions comme un outil pour prouver l’existence de solutions à des équations différentielles non linéaires, en mettant l’accent sur l’étude de l’exitence d’une solution positive d’un problème elliptique de type Kirchhoff mo délisant les vibrations de cordes élastiques. La méthodologie tourne autour de la construction d’une paire de fonctions (super solution et sous solution) qui encadrent la solution souhaitée, vient d’une suite monotone générée convergente.
Fundamental and applied mathematics
Keywords: sub-supersolution method; nonlinear differential equations; monotonic sequence; existence.; méthode des sous-super solutions; équations différentielles non linéaires; suite mono tone